Integration of Technology-Enabled Learning(TEL) at Higher education in developing countries: A case of Uganda Management Institute (UMI) - Kamya, Mwogeza Resty; Sansa Otim, Julian (Uganda Management Institute, 2019)
Globally, Higher Education Institutions have adapted Technology Enabled Learning (TEL) in their strategic plans so as to improve their learning outcomes as well as fit with the new trends of digitization. Uganda Management Institute (UMI) also followed suit, however, the feasibility of integrating TEL at UMI was still unknown. An institutional survey to establish UMI’s readiness to transform its pedagogical practices using TEL was therefore conducted on advisory of the Commonwealth of Learning (COL). A target population of 827 out of 3514 learners and 47 out of 59 faculty were surveyed and; institutional ICT Infrastructure and Policies audit was conducted. The findings indicated that UMI was developing preparedness, as it possessed some aspects of a TEL system, policy, and infrastructure. There existed a robust ICT infrastructure, however not well optimized for teaching and learning as staff used the laptops and desktops basically for PowerPoint presentations. Students expressed TEL readiness however , there existed inadequate ICT skills mostly among the facilitators. TEL such as Moodle, social media, OER existed but utilization remind undocumented and not shared. UMI, also lacked a specialized unit to offer TEL support to both the academic staff and students. This survey recommended that UMI’s management provides continued support to the enactment of the TEL policy; establishes a TEL steering committee to guide the TEL integration; staff students TEL capacity development; designing and development of TEL content and; establishes an institutional research cluster on TEL practices. This would enable UMI benefit from increased engagements between the students , facilitators and content hence improved learning outcomes.
Keywords: Integration of Technology-Enabled Learning(TEL); Higher education; Developing countries; Uganda Management Institute (UMI)